Maintaining Islamic Values within the Montessori Educational Institution - Fahruddin, Zuhri; Marjuki, Mochammad (LETIGES, 2025)
This study aims to discuss the Montessori Education Foundation, also known as Yapensori Jakarta, which modifies the curriculum from Maria Montessori. This study outlines how Yapensori maintains Islamic values. This study uses a qualitative approach with a case study type and data collection through interviews, observations, and documentation analysis. Researchers test the validity of the data using method triangulation and source triangulation techniques. Data analysis begins with reviewing the data and reducing it. Then, the data is arranged, after which the data is checked to ensure its validity and interpreted into a substantive theory. This study reveals that Yapensori applies the Montessori curriculum, namely emphasizing student development (humanistic) through maintaining noble morals, faith and piety, and supporting students' Islamic talents through calligraphy activities, reading the Qur'an before entering class, Muraja'ah Al-Qur'an before learning begins, congregational Ashar prayer, Muhasabah, saying greetings, getting used to discipline, extracurricular marawis, hadroh, and Tahfiz. This study is original in exploring the integration of Islamic values ​​in the Montessori education system in Yapensori, which is usually more humanistic and individualistic. This study highlights how Islamic values ​​are implemented through spiritual activities such as muraja’ah, tahfiz, and other worship practices. However, this study is limited to one institution, making it less generalizable. In addition, there has been no quantitative measurement of its impact on students' academics and character, and there is no comparison with non-Islamic Montessori. Further studies with a wider scope and mixed methods are needed for a deeper understanding.